Exchange Rate Pass-Through Over the Business Cycle in Singapore - Tan, Siang (IMF Working Papers; Working Paper ;, 2011)
This paper investigates exchange rate pass-through in Singapore using band-pass spectral regression techniques, allowing for asymmetric effects over the business cycle. First stage pass-through is estimated to be complete and relatively quick, confirming existing views that the exchange rate provides an effective tool to moderate imported inflation in Singapore. Asymmetric pass-through effects over the business cycle are also detected, with importers passing on a smaller share of exchange rate movements during boom periods as compared to recessions. This result suggest that Singapore's exchange rate policy could afford to "lean against the wind," especially during cyclical expansions.